QUECHUISMOS IN SPANISH: MORPHOSEMANTICS OF THE WORD "CACHACO" - Quintanilla Anglas, Rómulo (2009)
lt is through variation that naturallanguages show their tendency to change.The Spanish language, as any naturallanguage, presents variants that affect its system,especially, the lexicon. Precisely, one of che reasons thar has originated such a linguistic phenotnenon is the contact with the Quechua language. Today it is possible to observewords incorpora red in the DRAE that, with some structural modifications, have increasedour lexical system. Su eh is the case with the word "cachaco", English "cap" (of theQuechuan "kachaku") that, modified slightly in its original structure, is known in theHispanic area by a semantic content in which there underlies a pejorative feature absentin the Quechua system.